DISTRIBUTED TRUST IN ePAYMENTS SYSTEM - Vidya, K. P. (International Journal of Computing, 2014)
In this paper, a secret sharing scheme that is based on the Parallel Pollard rho Attack of the Elliptic Curve Discrete Logarithm Problem (ECDLP) is proposed for hierarchical access structures that can be activated dynamically. The shares of the scheme are distributed across two levels of participants but the reconstruction of the secret takes place at level zero which is the central processor or the trusted party of the scheme. The scheme finds its application in the Payments System of Banks and facilitates the replacement of paper cheques with eCheques. It also provides an efficient method of processing the payments at the Clearing House of Banks.